Programi nadaljnjega izobraževanja in usposabljanja učiteljev kot dejavnik profesionalnega razvoja - Pevec, Marija (Revija za elementarno izobraževanje, 2012)
The purpose of this article is to present the thoughts and the evaluation of teachers i. e. experienced practitioners regarding further education and training (FET) programmes as a significant factor in a teachers' professional development. The data for the qualitative survey which was conducted from December 2011 to February 2012, were collected with the help of semi-structured in-depth interviews with which the teachers have evaluated the quality of FET programmes, the influence of those programmes on practical work in class and presented their proposals for the improvement of the respective programmes. The concept of the survey was based on theoretical findings of the experts who deal with the factors of teachers' professional development as part of lifelong learning in which a teacher promotes students' quality knowledge at its best and develops their potentials through his/her own new knowledge acquisition and reflection on his/her work.
Keywords: education; učitelji; training; izobraževanje učiteljev; qualitative approach; strokovna usposobljenost; profesionalni razvoj